Stroke care is beyond clinical responsibility - Sowtali, Siti Noorkhairina (IIUM Press, 2024)
Stroke is defined as a clinical syndrome characterized by rapidly developing clinical symptoms and/or signs of focal, and at times global, loss of cerebral function, with symptoms lasting more than 24 hours or leading to death, with no apparent cause other than that of a vascular origin